Strategi Komunikasi dalam Pembelajaran Nahwu di Madrasah Ibtidaiyah Salafiyah Syafi’iyah Sukorejo Putra - Moch. Nuril Anwar; Wardani (Fakultas Dakwah Universitas Ibrahimy, 2024)
This article reveals the communication strategies used by the 4th grade Nahwu teacher at Madrasah Ibtidaiyah Salafiyah Syafi'iyah Putra in carrying out the learning process in class. Communication in education carried out by teachers and students is not just a process of exchanging and delivering learning material, but there are dimensions of the relationship between teachers and students which are the main conditions for creating an effective learning process. A good teacher is a good communicator or an effective teacher is an effective communicator in delivering learning material. Communication in teaching and learning activities (KBM) must be effective, both between teachers and students and between students themselves. Because the success of communication carried out by a teacher influences the success of the learning objectives themselves. To realize effective communication, a communication strategy is needed. So that student learning outcomes can increase in accordance with the curriculum and targets that have been determined. This research is field research using a qualitative approach. Data collection was obtained through observation, interviews and documentation as well as questionnaires. Apart from that, this article also aims to exchange ideas (sharing ideas) with the hope that the communication strategies that have been implemented can also be applied by other teachers in the process of teaching and learning activities. The results of the research show that the implementation of communication strategies carried out by the Nahwu teacher with students in class 4 i of Madrasah Ibtidaiyah Salafiyah Syafi'iyah Sukorejo Putra includes making the teaching book